Science Fiction as a Guide for AI, Personhood, and Moral Consideration - Backman-Daniels, Abigail (The Stellenbosch Socratic Journal, 2025)
Science fiction has long been a source of provocative speculation that has influenced our conceptions of both the present and future. It can thus be argued that both science fiction and philosophy are united in a search for understanding, even though they may go about this search quite differently. This article explores some possible contributions of science fiction to moral philosophy, specifically regarding the question of moral consideration. Particular focus is given to the issue of Artificial Intelligence and personhood, and a number of case studies are used in this investigation. Isaac Asimov's Laws of Robotics and the short story Cal (1995), as well as the Black Mirror episodes "White Christmas" (2014) and "Be Right Back" (2013) are used to explore some science fiction narratives relevant to moral philosophy. In this exploration, the importance and relevance of science fiction to society, not only as a source of entertainment but also as having philosophical relevance, is highlighted. This article concludes that science fiction ought to be taken seriously and consulted as a guide for navigating AI, personhood, and moral consideration in the near future, given its unique capacity to explore such issues.